Exploring the Role of Language Competence of Tourism Students in Enrolling in English-Taught Courses - Expósito-García, Alfonso; Sánchez-Cubo, Francisco (Taylor & Francis, 2025)
Acquiring adequate competence in foreign languages is crucial for professional development in the hospitality and tourism industry. Hence, most undergraduate programmes in tourism include English for Specific Purposes (ESP) and English as a Medium of Instruction (EMI) courses. Though there is literature on them, why students choose (or do not) to study English-taught courses has yet to be studied. This study addresses it using a sample of first-year students of the Bachelor of Tourism and probit models. The results show the statistically significant effects of the self-reported (subjective) level of language proficiency, the certified level of language proficiency and the previous experience of being taught in English on reducing the belief of being unable to attend an English-taught course successfully. Control variables (age, sex, income, and vocational choice) do not significantly impact. The study provides substantial evidence for academics and practitioners to improve tourism undergraduate programme curriculums and student selection.
https://openpolicyfinder.jisc.ac.uk/id/publication/25163
Keywords: Lengua inglesa técnica - Estudio y enseñanza; Lengua inglesa - Métodos; Turismo; English-taught courses; Language competence; Tourism; Higher education; English medium of instruction; English for specific purposes